Introduction to probability and statistics: from a Bayesian viewpoint - Lindley, D.V. (Cambridge: Cambirdge University Press, 1980)
Part. 1 Probability
Part. 2 Inference
Keywords: PROBABILIDAD; ESTADISTICA; BAYESIAN STATISTICS